National advocacy : a path to reform - Khan, Borhan Uddin; Asia Foundation (Bangladesh) (Dhaka : Asia Foundation, 2002)
With reference to Bangladesh.
Includes bibliographical references.
Keywords: Rural development -- Bangladesh; Non-governmental organizations -- Bangladesh; Social advocacy -- Bangladesh; Bangladesh -- Social policy